Cardiopulmonary resuscitation and response of health care professionals in district Chitral-Pakistan: a cross-sectional approach - Ahmad Khan, Aftab; Barolia, Robina; Afshan Nazar; Banu, Shafiqa (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the cardiopulmonary resuscitation response and performance experience among healthcare professionals in a secondary care setting. Method: The cross-sectional study was conducted from November 2019 to December 2020 in Chitral, Pakistan, and comprised healthcare professionals of either gender from selected hospitals in the remote hilly region. Data was collected using structured interviews based on 23 questions. Correct responses were scored 1, while incorrect or “don’t know” responses were scored 0. Data was analysed using SPSS 20. Results: There were 140 subjects with mean age 36.2±8.47 years (range: 23-57 years). There were 66(47%) nurses, 44(31%) paramedics and 30(22%) physicians. Physicians demonstrated superior knowledge compared to nurses and paramedics (p<0.05). Overall, there were 65(46%) participants who correctly identified when cardiopulmonary resuscitation should be initiated, indicating inadequate knowledge. Conclusion: There were significant gaps in cardiopulmonary resuscitation knowledge among healthcare professionals working in a secondary care setting. Key Words: Cardiopulmonary resuscitation, CPR, Cardiac arrest resuscitation, Basic life support, Advanced cardiac life support.